ON A DUST RICH REGION OF THE ORION NEBULA - MENDEZ, ME (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1965)
A region in the vicinity of Theta 2 Ori is studied to try to explain the differences in appearance between images below 3650 Å, and those at 5200 A. And it is concluded that there is an appreciable amount of dust close to the star.
BOL OBS TONAN TACUB
Keywords: RICH, REGION, ORION NEBULA; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS